Agua y desarrollo. El caso del Proyecto Olmos Tinajones (Lambayeque, Perú) - Urteaga Crovetto, Patricia (2022)
Since the early twentieth century, a developmentalist wave has attempted to mobilize both foreign aid and capital in Peru. Agriculture has been one of the sectors intervened to promote private investment through technological projects and institutional changes. An example of this phenomenon is the Olmos Tinajones Irrigation and Hidroenergy Project developed in the northern coast of Peru during the 1990s. In this article I outline two central arguments for the discussion on water and development: the institutional and physical transformations that occur in the water sector covertly encrypt asymmetries, and the discourse of the common good that legitimize huge hydraulic projects is eventually captured by corruption schemes that primarily benefit private companies.